Analisis Kebijakan Pendidikan Islam Dalam Perspektif Integrasi-Interkoneksi: Peran UIN Sunan Kalijaga Sebagai Implementasi Tri Darma Perguruan Tinggi - Eni Fitria; Sutrisno (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
The level of education in higher education is to produce students who can contribute to society who have expertise in various academic This study aims to look at the integration-interconnection in the Tri Dharma of higher education in solving the problem of the dichotomy of science at UIN Sunan Kalijaga Yogyakarta. The purpose of this research is to find out the role of Tri Dharma in solving the problem of dichotomy of knowledge at UIN Sunan Kalijaga Yogyakarta. Qualitative research method with a library research approach. Data collected from other books, journals, literature, notes and results of relevant research reports. The results of the Interconnection Integration at UIN Sunan Kalijaga has become a core value, both in Islamic science and secular science from this concept that can realize comprehensive thinking and can be poured into the Tri Dharma of Higher Education so as to make the entire academic community qualified and can be a role model for the community and the surrounding environment.